Phylogenetic relationships of the Orang Asli in Taman Negara based on Alu8 biallelic markers / Aisyah Mohd Ismail - Mohd Ismail, Aisyah (2017)
The Orang Asli is a collection of ethnic groups that are believed to be the indigenous people of Peninsular Malaysia. They consist of three different ethnics which are Senoi, Proto-Malay (or also known as the Aboriginal Malay) and Negrito. Till now, there is very few research carried out in Malaysia involving Orang Asli population. Recent studies only focused on haplotype diversity of Y-STRs in Malays of Kelantan and Minang. For many years, there are many changes on Orang Asli population in Peninsular Malaysia. The reason for these changes maybe due to the Orang Asli migration, Orang Asli communities living together in the village and Orang Asli neighbourhood with adjacent village or states. Hence, there is an urgent need for study on the genetic and evolutionary history of Orang Asli population. In this study, the evolutionary history and relationship among Orang Asli in Taman Negara is based on the Alu insertion polymorphisms specific to chromosome 8. Alu bi-allelic markers are generally most preferred among other markers, as there is no known mechanism of back-mutation reported which means that they are identical by descent markers. This research focused on the highest population of Orang Asli which resides in Taman Negara, Pahang. The analysis includes the distribution of Alu polymorphisms specific on chromosome 8 (by using PCR) in forty-nine samples of Orang Asli and also the genetic distance between (Bateq and Semoq Beri) tribes of Orang Asli in Taman Negara. Results revealed that a total of twenty-one Orang Asli individuals contained APO insertion. Whilst, fourteen Orang Asli individuals contained FXIIIB insertion. Furthermore, there were significant differences in the Alu FXIIIB element compared to the Alu APO element of Orang Asli population based on the phylogenetic trees construction. It can be concluded that outbreeding might have occurred between the Bateq and Semoq Beri tribes of Orang Asli population in Taman Negara. This is because, the genetic distances of Alu APO and Alu FXIIIB sequences between both tribes are closer to each other. Further study is to be taken up on large population of Orang Asli in various geographical areas of Peninsular Malaysia for heterozygosity.